(untitled) (Research, Society and Development, 2019)
This paper aims to work the role of the pedagogical supervisor, initially, from the legal and theoretical approach. Following this explanation, the article discusses the work of the supervisor at school. The methodology used was literature review and document analysis: regulations, legislation and edicts. The objective of this work was to legally and theoretically identify the role of the supervisor in the Minas Gerais State School. The results achieved were that the presence of the pedagogue in the school environment is essential to think and collectively build educational practices. The final considerations implies that it is necessary for the school community to know the work of the pedagogue in the construction of meaningful and punctual educational practices for the school community, requiring from this educator a posture of teamwork to realize the projects in a collective way and thought by the collective to the collective.